LEMBAGA PENDIDIKAN KEAGAMAAN WARISAN ORANG ARAB - Wardiah Hamid (Balai Penelitian dan Pengembangan Agama Makassar, 2018)
This paper is intended to trace the existence of Hadramaut in South Sulawesi,how exist their descendants survive until now and how they build religiouseducation institutions throughout the region in South Sulawesi. They are ableto fluid with local people playing their role as Muslim community inNusantara without any gap between indigenous society. The Hadramautcommunity that is already mingling with the local community builds an Arabvillage. They are then known in the archipelago as Arabs, among them somewho retain the lineage and some others are not defending anymore. Theapproach taken in this research is qualitative deskriftip. The results of thisstudy show the Arab descendants that still exist today among Al-Habsyi, AlHamid, Al Kaf, As Soyfi, Bin Shal, Asy Syihab, Al Aidid, Assaggaf, AlMakdali, Al Bahagi, Basalamah, Al Katiri, At Tamimi, Bahweres, Al Amudi,Al-Kat'a, Shadaqa, Al Asus, As Siraj. And some of them manage Religiouseducation institutions in South Sulawesi. Several Religious Educationinstitutions have been established and are still managed by Arab descentthroughout the region in South Sulawesi.